2021
DOI: 10.3390/cancers13122933
|View full text |Cite
|
Sign up to set email alerts
|

Octogenarians’ Breast Cancer Is Associated with an Unfavorable Tumor Immune Microenvironment and Worse Disease-Free Survival

Abstract: Elderly patients are known to have a worse prognosis for breast cancer. This is commonly blamed on their medical comorbidities and access to care. However, in addition to these social issues, we hypothesized that the extreme elderly (octogenarians—patients over 80 years old) have biologically worse cancer with unfavorable tumor immune microenvironment. The Cancer Genomic Atlas (TCGA) and the Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) breast cancer cohorts were analyzed. The control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…At present, there is still controversy about the age of CLBC. Some scholars have found that patients with CLBC are younger than patients with other subtypes (114,115,117,118). However, Xu et al (119) found that the age of CLBC patients is not significantly different from other subtypes, which may be related to their small sample size.…”
Section: Clinicopathological Characteristics Of Claudin-low Breast Ca...mentioning
confidence: 97%
See 1 more Smart Citation
“…At present, there is still controversy about the age of CLBC. Some scholars have found that patients with CLBC are younger than patients with other subtypes (114,115,117,118). However, Xu et al (119) found that the age of CLBC patients is not significantly different from other subtypes, which may be related to their small sample size.…”
Section: Clinicopathological Characteristics Of Claudin-low Breast Ca...mentioning
confidence: 97%
“…At present, there is still controversy about the age of CLBC. Some scholars have found that patients with CLBC are younger than patients with other subtypes ( 114 , 115 , 117 , 118 ). However, Xu et al.…”
Section: Clinicopathological Characteristics Of Claudin-low Breast Ca...mentioning
confidence: 99%
“…Macrophages are highly plastic and can differentiate into two “activation” states—pro-inflammatory (M1) macrophages and anti-inflammatory (M2) macrophages [ 68 ]. A study based on elderly breast cancer patients found that, compared to the younger control group, breast cancer patients aged older than 80 had a poorer tumor immune microenvironment and significantly higher infiltration of M2 macrophages [ 10 ]. M2 macrophages can promote the metastasis of breast cancer cells in vitro and in vivo by secreting chitinase 3-like protein 1 (CHI3L1), which interacts with interleukin-13 receptor α2 chain (IL-13Rα2) molecules on the plasma membrane of cancer cells [ 69 ].…”
Section: The Effect Of Aging Microenvironment On Breast Tumorigenesis...mentioning
confidence: 99%
“…Investigating the impact of aging on the tumor microenvironment is interesting and valuable. In recent years, an increasing number of studies have been conducted on the influence of the aging microenvironment on various cancers, including breast cancer [ 8 , 9 , 10 ]. Aging is a physiological degradation process characterized by genomic instability, telomere attrition, epigenetic alterations, loss of proteostasis, deregulated nutrient sensing, mitochondrial dysfunction, cellular senescence, altered intercellular communication, and stem cell exhaustion [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liposits and colleagues showed that upfront dose-reduced chemotherapy in the NORDIC9 randomized trial resulted in a better quality of life and physical functioning compared to full-dose chemotherapy in patients with metastasized colorectal cancer [ 16 ]. Additionally, the study by Okano investigated differences in outcomes between younger and older patients with breast cancer, and showed that octogenarians had unfavorable tumor micro environment profiles and a worse survival [ 17 ].…”
mentioning
confidence: 99%